Organizational Change at the Educators Professional Development Center in West Java - Rosyidah Halim, Ima; Nina Karlina; Ramadhan Pancasilawan (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2025)
Organizational change is a strategy and implementation aimed at transforming the organization to enhance the empowerment and development of educators and other educational staff. This aligns with the Ministry of Education, Culture, Research, and Technology Regulation Number 14 of 2022 concerning the Organizational Structure of the Educators Professional Development Center. The objective of this research is to ascertain the effectiveness of the organizational changes implemented at the Educators Professional Development Center in West Java. This research draws on the organizational change Theory by  Jones (2013). The method employed in the study is a qualitative approach using purposive sampling. The findings indicate that organizational changes in the dimensions of functional resources remain ineffective because of a lack of integration between work teams, so it is necessary to form work teams and assign responsible parties to ensure that activity goals are achieved in accordance with the head's performance agreement and the functions of the Educators Professional  Development Center in West Java.